An Expedient Access to Still–Gennari Phosphonates - Messik, Frauke; Oberthür, Markus (Synthesis, 2013)
An inexpensive and efficient route to the Still–Gennari phosphonates, methyl and ethyl bis(2,2,2-trifluoroethyl)phosphonoacetates, has been developed. This short reaction sequence is operationally simple and makes these versatile reagents for the preparation of Z-alkenes, according to the Still–Gennari modification of the Horner–Wadsworth–Emmons olefination reaction, available in multigram quantities.
Keywords: Z-alkenes; olefination; phosphorus; Horner–Wadsworth–Emmons reaction; Still–Gennari modification